Obsidian : Geology and Archaeology in the North American Southwest - Shackley, M. Steven (Book collections on Project MUSE., 2005)
"Obsidian was long valued by ancient peoples as a raw material for producing stone tools, and archaeologists have increasingly come to view obsidian studies as a crucial aid in understanding the past. Steven Shackley now shows how the geochemical and contextual analyses of archaeological obsidian can be applied to the interpretation of social and economic organization in the ancient Southwest." "This book, the capstone of decades of investigation, integrates a wealth of obsidian research in one volume. It covers advances in analytical chemistry and field petrology that have enhanced our understanding of obsidian source heterogeneity, presents the most recent data on and interpretations of archaeological obsidian sources in the Southwest, and explores the ethnohistorical and contemporary background for obsidian use in indigeneous societies."--Jacket.